Muhammad : the messenger of God - Kelen, Betty (Singapore : Graham Brash, 1989)
A biography of the founder of Islam dealing with the life of the man and the religion and civilization he shaped
Bibliography: p. 281
Keywords: Muhammad, -- Prophet, -- d. 632 -- Juvenile literature; Muhammad, -- Prophet, -- d. 632.; Muslims -- Saudi Arabia -- Biography